Improving Students’ Mastery Of English Punctuation Using Granded Written Exercises - M. Dahlan Bahang; Arma Amir Hamzah (Celebes of Linguistics Journal, 2019)
This study was intended to answer the research questions namely ; (1) which punctuation are found difficult for the students?, (2) do graded written exercises improve the students” mastery of punctuation?, (3) are the students interested in learning English punctuation through graded written exercises?. This study employed a pre-experimental method. The population consisted of the third year students of SMP Negeri 33 Makassar . The number of the population was four classes which consisted of forty students each class. The sample was taken by using cluster sampling: ten students of each class were selected randomly to become the sample of the study. The result of the study were (1) punctuation that was found difficult for the students included question mark, quotation mark and exclamation point (2) graded written exercises improve the students’ mastery of punctuation, (3) the students were interested in learning English punctuation through graded written exercises. The researcher concluded that the use of English punctuation is very difficult for the students particularly in long sentences. Therefore, they have to be trained and use the punctuation in sentences appropriately.